Research of Specifics of Management of Regional Development for the Purpose of Observance of Reproduction Proportions - Novoselov, Sergey N.; Shtapova, Irina S.; Kovalenko, Alla A.; Medyanik, Natalya V.; Ram, Oleg L. (International Review of Management and Marketing, 2016)
In this article theoretical and methodological approaches to definition of the region essence are developed. The author has studied the integration processes in regional economic system from a position of an assessment and the analysis of meso-economic systems as sets of spatial and organized structures. The contents and concept of stability of the market considering hardships from the modern globalization are also specified. Results of research provide reasoned and evidential proof to the concept of the region as open multicomponent system of the local markets functioning in the uniform industrialist environment formed by the climatic, social and economic, historical and political and other factors typical for any subject of the Federation. Region also is viewed as the participant of integration process that creates organizational and economic prerequisites of a sustainable development of regional social and economic system regarding improvement of management of the local markets, including the market of ecological goods and services. Keywords: regional development, reproduction, regional policy, sustainable development JEL Classifications: G32; O30